Improvement of English Speaking Ability In 7th Grade Students of Ganesha Junior High School Denpasar Through TANDUR Method - I Putu Hartomi Arya Franata; I Wayan Simpen; Ni Made Dhanawaty (The Doctoral Studies Program of Linguistics of Udayana University, 2020)
This study aims to determine the application of theTANDUR method can improve speaking skills inlearning English. This research is a qualitative studyusing five types of methods which include tests,TANDUR experiments, questionnaires, interviews, andobservations. The results of the questionnaire answeredby students showed the factors that influence theirmotivation in the learning process. The factors thatinfluence students in the learning process are dividedinto two, namely internal factors and external factors.Based on the results of the study, it can be concludedthat the ability of students in speaking Englishincreases after the application of the TANDURmethod. Three aspects of speech assessed in this study,were grammar, vocabulary, and understanding thatexperienced an increase, both in class 7.1 which is thetreatment class and class 7.3 which is the control class.